The Impact of PPG Program on the Performance of Pre-Service and In-Service English Teachers Based on Teacher’s Self-Assessment - Nurhaini Widia Putri; Sitti Fatimah (Journal of English Language Teaching, 2021)
The PPG (Pendidikan Profesi Guru) program is a government effort to improve the quality of education in Indonesia by increasing teacher professionalism. The purpose of the PPG program itself is to overcome problems in the world of education. This research is conducted to obtain information from English teachers in West Sumatra who have graduated from the PPG Program at least two years ago (from 2019 backwards) regarding the impact of PPG program on English teachers’ pedagogical and professional competencies. 45 in-service and 11 pre-service English teachers have been involved as the sample of this research. The type of this research is survey research with quantitative method. The data were collected by using close-ended and open-ended questionnaire distributed through Google-form. The findings of this research show that UNP PPG Program has impacted decently on English teachers' performance and improved their professional and pedagogical competencies. Although there are some teachers who assess their teaching performance as not good enough in several points of the statement in the questionnaire, most of the results show that the UNP PPG Program has improved the teaching performance of English teachers. The results and findings from this study are expected to improve the process of conducting PPG program and pay more attention to the impact that will be received by PPG graduates.